Applicability evaluation of Cupressus lusitanica for pulp production - Faedo de Almeida, Caio Cesar; D’Angelo Rios, Polliana; Bayestorff da Cunha, Alexsandro; Melo Ampessan, Camilla Gabriela; Spanhol, Alana (Maderas. Ciencia y Tecnología, 2016)
This paper aimed to study Cupressus lusitanica wood tracheids biometrics along radial direction and chemical analysis in order to encourage the use of new forest species for pulp production in southern Brazil. Axial tracheids anatomical analysis was held in 3 positions, in the pith-periphery direction. Total length, total diameter and lumen diameter were analyzed, and wall thickness, flexibility coefficient, wall fraction, felting index and Runkel’s ratio were calculated based on these variables. Chemical analysis determined total extractives, sodium hydroxide attack degree, ash, lignin and holocellulose content. For anatomical variables, a statistically significant increase in the pith-periphery direction was observed for total length (L = 5,85mm), for total diameter (D = 47,18 μm), lumen diameter (d = 32,92μm) and wall thickness (e = 14,26μm) was observed stabilization from intermediate section. The species was characterized as with high rigidity tracheids (WF = 61,73%), although being considered “good” for wood pulp production (RI = 0,93). The chemical composition showed high lignin content (L = 36,21%) and low holocellulose content (H = 59,19%). Cupressus lusitanica wood showed appropriate anatomical characteristics to be part of the pulp industry raw material supply. However, chemical properties may compromise the species use due to high lignin content.